Abuse, neglect and exploitation in assisted living: an examination of long-term care ombudsman complaint data. Issue 3 (27th May 2019) - Magruder, Karen J.; Fields, Noelle L.; Xu, Ling
Abstract: Long-term care ombudsmen are advocates who empower and assist residents with complaints relating to quality of care and violations of resident rights in assisted living (AL) and skilled nursing facilities (SNF). Given that long-term care residents are vulnerable to elder abuse, neglect and exploitation (ANE), and existing gaps in the literature addressing ANE in AL, more research is needed to understand the prevalence of ANE in these communities. Ombudsman complaint data (n = 140, 497 complaints) in 3, 171 Texas long-term care facilities were analyzed using proportion Z tests. Findings showed that SNF had higher rates of ANE per resident. For both AL and SNF, verbal/psychological abuse was the most reported type of ANE and sexual abuse was the least reported. AL residents had disproportionately high rates of financial exploitation. We explored factors that may contribute to these findings and recommend strategies for preventing ANE.